International Conference on Word-Formation in Košice 2025 - Inčiuraitė-Noreikienė, Lina (Respectus Philologicus, 2026)
From 25 to 28 June 2025, the conference “Word-Formation Theories VII & Typology and Universals in Word-Formation VI” was organised by the Department of British and American Studies, Faculty of Arts, Pavol Jozef Šafárik University in Košice, in cooperation with SKASE (Slovak Association for the Study of English). The main organisers were Pavol Štekauer, Lívia Körtvélyessy and Slávka Tomaščíková. The conference focused on developments in word-formation theories. In June 2025, the conference celebrated its 20th anniversary, marking two decades since its inaugural edition, which highlighted the state of the field alongside the publication of Handbook of Word-Formation (Štekauer and Lieber, 2005, Dordrecht: Springer).